Asymmetric Double Hydroxycarbonylation of Alkynes to Chiral Succinic Acids Enabled by Palladium Relay Catalysis. (20th May 2022) - Ji, Xiaolei; Shen, Chaoren; Tian, Xinxin; Zhang, Hongru; Ren, Xinyi; Dong, Kaiwu
Abstract: A Pd‐catalyzed asymmetric double hydroxycarbonylation of terminal alkynes was developed by using relay catalysis, providing a highly efficient route to chiral succinic acids (41 examples, 76–94 %, 94–99 % ee ). Key to success was the combinatorial use of a Pd precursor with two distinct phosphine ligands in one pot. The synthetic utilities of this protocol were showcased in the facile synthesis of key intermediates for chiral pharmaceuticals. Abstract : By combining two distinct phosphine ligands, a Pd‐catalyzed asymmetric double hydroxycarbonylation of terminal alkynes to chiral succinic acids was achieved in a one‐pot manner. The alkyne carbonylation was dictated by the achiral monophosphine to afford branched acrylic acids, while the resulting intermediates further underwent Pd/chiral bisphosphine‐catalyzed enantioselective hydroxycarbonylation.